Internal Influence Locus of Control And External Locus of Control Towards Organizational Citizenship Behavior (OCB) In The Office of Small And Medium Business Cooperations, West Kalimantan Province - Prianti, Neni; Mahdi, Irfan (Dinasti International Journal of Economics, Finance & Accounting, 2024)
This research presents important findings regarding the relationship between Internal Locus of control (X1), External locus of control (X2) and Organizational Citizenship Behavior (OCB) (Y). The sample in this research was based on employees at the West Kalimantan Province Small and Medium Enterprises Cooperatives Service, totaling 58 respondents. The sampling technique in this research is Saturated Sampling. Further research is needed to understand more deeply the dynamics underlying the observed phenomena. The results of data analysis and discussion show that there is a positive influence of Internal Locus of Control on Organizational Citizenship Behavior (OCB) and External Locus of Control has a positive influence on Organizational Citizenship Behavior (OCB). The data obtained were analyzed using SPSS 25.